PTP1B: a new therapeutic target for Rett syndrome - Lutz Tautz (The Journal of Clinical Investigation, 2015)
Rett syndrome (RTT) is an X-linked neurodevelopmental disorder that is characterized by successive loss of acquired cognitive, social, and motor skills and development of autistic behavior. RTT affects approximately 1 in 10,000 live female births and is the second most common cause of severe mental retardation in females, after Down syndrome. Currently, there is no cure or effective therapy for RTT. Approved treatment regimens are presently limited to supportive management of specific physical and mental disabilities. In this issue, Krishnan and colleagues reveal that the protein tyrosine phosphatase PTP1B is upregulated in patients with RTT and in murine models and provide strong evidence that targeting PTP1B has potential as a viable therapeutic strategy for the treatment of RTT.